2020
DOI: 10.1038/s42003-020-1009-y
|View full text |Cite
|
Sign up to set email alerts
|

Population genomics of Staphylococcus pseudintermedius in companion animals in the United States

Abstract: Staphylococcus pseudintermedius is a commensal bacterium and a major opportunistic pathogen of dogs. The emergence of methicillin-resistant S. pseudintermedius (MRSP) is also becoming a serious concern. We carried out a population genomics study of 130 clinical S. pseudintermedius isolates from dogs and cats in the New England region of the United States. Results revealed the co-circulation of phylogenetically diverse lineages that have access to a large pool of accessory genes. Many MRSP and multidrug-resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 69 publications
5
27
0
Order By: Relevance
“…Almost 85% and 23% of isolates in the current study harbored bla Z and mec A genes, respectively. These findings supported those of Smith et al 34 . The previous study also showed a high percentage (over 80%) of multidrug-resistant isolates among MRSPs 7 .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Almost 85% and 23% of isolates in the current study harbored bla Z and mec A genes, respectively. These findings supported those of Smith et al 34 . The previous study also showed a high percentage (over 80%) of multidrug-resistant isolates among MRSPs 7 .…”
Section: Discussionsupporting
confidence: 92%
“…This result corresponded to the frequent presence of genetic determinants of tetracycline resistance in isolates from healthy cats. The widespread presence of tet (K) and tet (M) in S. pseudintermedius isolates was previously described 34 . S. pseudintermedius isolates from sick animals were more frequently phenotypically and genetically resistant to beta-lactams, limiting the successful application of antibiotics in treatments.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Both MRSA and MRSP display resistance to β-lactam and many non-β-lactam antimicrobial classes, such as fluoroquinolones, aminoglycosides, tetracyclines, sulfonamides, macrolides, and lincosamides (18)(19)(20)(21)(22). However, MRSP isolates from companion animals have been reported to be more multidrug-resistant than MRSA (23). A recent study has revealed that many clinical MRSP multidrug-resistant clones have emerged through multiple independent, horizontal acquisition of resistance determinants and frequent genetic exchange that disseminate DNA to the broader population (24).…”
Section: Introductionmentioning
confidence: 99%
“…The global emergence and rapid dissemination of MRSP is a serious health threat in veterinary and human medicine [ 2 , 12 , 13 ]. Remarkably, MRSP and other multidrug-resistant clones of various sequencing types are spreading globally with steadily increasing incidence and prevalence rates in both healthcare and community settings [ 2 , 13 , 45 , 46 ]. Although large-scale genome sequencing projects and several epidemiological studies have gained new insights into the complexity of MRSP evolution and diversity, general understanding of S. pseudintermedius virulence and immune evasive attributes is still very limited.…”
Section: Discussionmentioning
confidence: 99%